SMART HYDROPONIC BERBASIS ANDROID DI SMKN 6 KENDAL - Muhammad Aji Saputra; Eko Riyanto; Solikhin (Universitas Islam Nahdlatul Ulama Jepara, 2022)
The rapid development of technology makes people innovate to make new things and leave old ways to simplify and save time a job. One example is monitoring the value of pH, PPM, room temperature and humidity as well as water temperature of hydroponic plants that used to still use conventional tools, now switching to Android-based IoT technology (Smart Hydroponics), especially at SMKN 6 Kendal. IoT is a way of connecting the Arduino sensor modules needed for hydroponic cultivation, where the results of sensor readings will be actually sent to the user's Android smartphone. The Arduino sensors are pH, TDS, DHT 11, ds1820 sensors. With this smart hydroponics, it is hoped that it can help hydroponic cultivators in the SMKN 6 Kendal environment to monitor their gardens anywhere and anytime and control the hydroponic temperature to be maintained below 30 degrees. From the reading of the value of the smart hydroponic sensor, it works well with existing standards and through MAPE calculations with a value below 10%.